1991
DOI: 10.1295/polymj.23.211
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Characterization of Thermally Stable Polymers through Anionic Polymerization of tert-Alkyl Crotonates

Abstract: ABSTRACT:Some alkyl crotonates bearing tert-alkyl groups, i.e., lert-butyl, tert-amyl, 1-adamantyl and 3,5-dimethyl-1-adamantyl crotonates were prepared and polymerized with sec-butyllithium as an anionic catalyst in toluene or THF. The resulting polymers were confirmed to consist of poly(substituted methylene) structure by IR and NMR spectroscopies. The polymers bearing adamantyl groups had more resistance to hydrolysis, whereas the tert-butyl and amyl esters were readily hydrolyzed. The introduction of the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

1991
1991
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 31 publications
0
13
0
Order By: Relevance
“…The 1,2‐disubstituted olefins are expected to have a lower reactivity than vinyl double bonds but in fact appear to be inert toward radical thiol‐ene chemistry, unlike the double bonds in 1,4‐polybutadiene (cross‐linking), polynorbornenes or other ROMP prepared polymers (quantitative addition of thiols) . A nucleophilic or base‐catalyzed thiol‐Michael addition of MMP to 4 was not attempted because it was expected to fail or complicated by side reactions (as known for the anionic polymerization of alkyl crotonates) . Double bonds were, however, quantitatively consumed during the reaction with bromine.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The 1,2‐disubstituted olefins are expected to have a lower reactivity than vinyl double bonds but in fact appear to be inert toward radical thiol‐ene chemistry, unlike the double bonds in 1,4‐polybutadiene (cross‐linking), polynorbornenes or other ROMP prepared polymers (quantitative addition of thiols) . A nucleophilic or base‐catalyzed thiol‐Michael addition of MMP to 4 was not attempted because it was expected to fail or complicated by side reactions (as known for the anionic polymerization of alkyl crotonates) . Double bonds were, however, quantitatively consumed during the reaction with bromine.…”
Section: Resultsmentioning
confidence: 99%
“…Double bond isomerization is seemingly to fail [ 20 ] or complicated by side reactions (as known for the anionic polymerization of alkyl crotonates). [ 22 ] Double bonds were, however, quantitatively consumed during the reaction with bromine.…”
Section: Polymerizations (General Procedures)mentioning
confidence: 99%
“…97 The presence of the β-methyl substituent on the unsaturated group induces steric hindrance with the α-substituent. 98 However, the carboxylic acid terminated PHB oligomers produced by thermal degradation can be subsequently modified to give methacrylic PHA macromonomers. The graft copolymers containing PHAs can obtained by copolymerization of PHAs macromonomers with other (meth)acrylic family members.…”
Section: ■ Chlorination Of Phasmentioning
confidence: 99%
“…However, β-substituted α,β-unsaturated carboxylate monomers, such as alkyl crotonates and alkyl cinnamates, are not easily polymerized. , In fact, alkyl crotonates cannot be polymerized by the common radical initiators of azobisisobutyronitrile (AIBN) and rac -2,2′-azobis­(4-methoxy-2,4-dimethylvaleronitrile) (V-70L) (see Supporting Information). Moreover, in the past two decades, synthetic methods for poly­(alkyl crotonate)­s (PRCrs) have been infrequently studied. In one study, Ute et al showed that transition-metal Lewis acids, such as HgI 2 , catalyzed the GTP of various n -alkyl crotonates using 1-trimethylsiloxyl-1-methoxy-2-methyl-1-propene (MTS) as an initiator. In this study, we attempted the GTP of various alkyl crotonates with organic catalysts. Herein, we demonstrate a synthetic procedure for PRCrs by GTP using organic superacid catalysts (Scheme ) and characterize the obtained PRCrs.…”
Section: Introductionmentioning
confidence: 99%